DESIGN OF SOLAR POWERED AUTO IRRIGATION SYSTEM - Shivani Maharnavar, Sonal Metakari, Pratidnya Navale, Payal Salgare (International Journal of Innovations in Engineering Research and Technology, 2022)
Farmers are now facing the problem of power outages and water shortages. So, we use an Auto irrigation system using solar energy and a soil moisture sensor. Soil moisture sensor will detect soil moisture level and send a signal to the PIC microcontroller and the engine will ON / OFF automatically shut down. If the field is dry the LCD will show Motor is ON and if the field is wet the LCD will show Motor is CLOSED.